2015
DOI: 10.1097/wnr.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic and endocannabinoid neuromodulatory effects overlap on neurons of the pedunculopontine nucleus of mice

Abstract: The pedunculopontine nucleus (PPN) is a part of the reticular activating system (RAS) and one of the main sources of the cholinergic fibers in the midbrain, while it is also subject to cholinergic modulation. This nucleus is thought to have an important role in REM sleep and wakefulness. Several neuromodulatory mechanisms were described in the PPN, but overlaps of the endocannabinoid and cholinergic effects have not been demonstrated yet.We showed that PPN neurons respond to carbachol in a heterogeneous way: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Also surprisingly, we found that changes in SIC frequency and area by neuromodulatory actions depend on previous SIC activity and not on the neuromodulatory agent itself: if original SIC activity was high, neuromodulatory actions decreased it, while in case of low SIC activity, neuromodulatory agents had a stimulatory action on them. Explaining these results along with the previously obtained data (Kőszeghy et al, 2015 ; Kovács et al, 2015 , 2017 ), we hypothesize that neuromodulatory actions increase ambient glutamate level, which stimulate appearance of SICs by activating NMDA receptors, if the majority of NMDA receptors are available for activation. However, if NMDA receptors are already activated by a previously increased ambient glutamate level, further glutamate increase results NMDA receptor desensitization/inactivation.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Also surprisingly, we found that changes in SIC frequency and area by neuromodulatory actions depend on previous SIC activity and not on the neuromodulatory agent itself: if original SIC activity was high, neuromodulatory actions decreased it, while in case of low SIC activity, neuromodulatory agents had a stimulatory action on them. Explaining these results along with the previously obtained data (Kőszeghy et al, 2015 ; Kovács et al, 2015 , 2017 ), we hypothesize that neuromodulatory actions increase ambient glutamate level, which stimulate appearance of SICs by activating NMDA receptors, if the majority of NMDA receptors are available for activation. However, if NMDA receptors are already activated by a previously increased ambient glutamate level, further glutamate increase results NMDA receptor desensitization/inactivation.…”
Section: Discussionsupporting
confidence: 77%
“…Cholinergic stimulation resulted depolarization or hyperpolarization on PPN neurons, leaving a distinct neuronal population unaffected (Ye et al, 2010 ). Cannabinoid agonists exerted similar actions on the PPN, showing marked overlap with the cholinergic actions (Kőszeghy et al, 2015 ; Kovács et al, 2015 , 2017 ). In overlap with carbachol-initiated hyperpolarization, serotonin also elicited tonic hyperpolarization on the same PPN neurons (Leonard and Llinás, 1994 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…There are more overlaps of neuromodulatory actions in the PPN. Orexin and ghrelin (Kim et al, 2009 ), or endocannabinoid and cholinergic actions depolarize the same neuronal population (Kovács et al, 2015 ). The similar regulation of the M-current might have a role in overlaps of the neuromodulatory effects on PPN neurons.…”
Section: Discussionmentioning
confidence: 99%